Tingkat Kepuasaan Mahasiswa STIT Syamsul Ma’arif Bontang terhadap Pelaksanaan Ujian Skripsi Tahun 2025 - Ihsan, Muh.; Permana, Kiki (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to determine the level of student satisfaction at STIT Syamsul Ma’arif Bontang regarding the implementation of the thesis examination in 2025. The research employed a descriptive quantitative method with a survey approach. Data were collected through questionnaires distributed to students who had participated in the thesis examination. The results show that the majority of students were very satisfied with various aspects of the examination. Information regarding the examination schedule was delivered clearly and on time (81.3%), the registration process was easy to understand and access (65%), the examination was held according to the scheduled time (100%), and the examination room facilities were considered very satisfactory (78.1%). In addition, supervision by academic advisors before the examination was very helpful (71%), and the overall service provided during the thesis examination at STIT Syamsul Ma’arif Bontang was rated as very satisfactory (71.9%).